EFFORTS TO IMPROVE POETRY WRITING SKILLS BY USING CTL METHOD OF GRADE VII STUDENTS OF SEMESTER II SMPN 2 SENDANGAGUNG - Puspita, Dian (JLCEdu (Journal of Learning and Character Education), 2021)
The essence of Indonesian language learning is learning to communicate and literature to appreciate people. One of the skills that need to be mastered by junior high school students is to write poems related to the beauty of nature. The purpose of this research is to improve the ability of students in Writing Poetry of Natural Beauty with the approach of CTL (Contextual Teaching and Learning) SMP Negeri 2 Sendangagung Sendangagung Subdistrict. This research method uses Class Action Research (PTK) which is researching about students' teaching and learning activities in Writing Poetry of Natural Beauty with CTL (Contextual Teaching and Learning) approach. The population in this study is all students of grade VII Semester II SMP Negeri 2 Sendangagung Sendangagung Subdistrict, with the number of samples taken as many as 32 students. Analyze the data that the author performs by calculating the level of completion per indicator and comparing the results of each cycle performed. Based on the analysis of research data that the author can conclude that there is an increase in the ability of grade VII students of Semester VII SMP Negeri 2 Sendangagung Sendangagung Subdistrict in writing poems related to natural beauty. The average score of the first test was 67.4 with a percentage of completion reaching 60.6%. The average score of the second test was 68.35 with a completion percentage of 87.8%. The average score of the third test was 71.72 with the number of students achieving completion as many as 33 students and the percentage of completion reached 100%.  This indicates an increase in students' ability to write poetry about the beauty of nature.